Antitumor Effects and the Compatibility Mechanisms of Herb Pair Scleromitrion diffusum (Willd.) R. J. Wang–Sculellaria barbata D. Don - Lu, Li; Zhan, Sheng; Liu, Xiaohui; Zhao, Xin; Lin, Xiukun; Xu, Huanli (Frontiers in Pharmacology, 2020)
Herb pair Scleromitrion diffusum (Willd.) R.J.Wang (HD) and Scutellaria barbata D. Don (SB) has been most frequently used for cancer treatment in traditional Chinese medicine (TCM). This study aimed to explore the in vitro and in vivo antitumor effects of HD-SB extract and to elucidate the underlying compatibility mechanisms. HD, SB, and HD-SB extract were prepared, and the components were detected by ultra performance liquid chromatography coupled with quadrupole time-of-flight mass spectrometry (Q-TOF/MS) method. The in vitro antitumor effects of various concentrations of these extract were detected on several tumor cell lines using MTS assay. The in vivo antitumor effects were evaluated in Panc28 cells bearing nude mice model. The compatibility mechanisms of herb pair HD-SB were evaluated based on the systems pharmacology strategy, and then validated by cellular experiments. HD-SB extract was demonstrated to inhibit the proliferation of the cancer cell lines dose-dependently by MTS assay. In vivo antitumor effects of HD-SB was much more potent than either of the two single herbs in Panc28 xenograft mice model. A total 29 active ingredients involved in anti-tumor effects were selected from HD and SB, and the “herb-composition-target-disease” network was constructed. Then, 58 cancer-related targets and 66 KEGG pathways were identified and PTGS2, HSP90, EGFR, MMP2, PPAR-γ, and GSTP mediated pathways were predicted to be the antitumor mechanisms of HD-SB. The cellular experiments showed that HD-SB significantly induced cancer cell apoptosis, decreased p-EGFR, HSP90 and bcl-2 expressions, and increased PPARγ, bax, cleaved caspase 3, cleaved PARP, p-AKT and p-PI3K expressions compared with HD or SB treatment. Our study showed that HD-SB inhibited tumor growth both in vitro and in vivo, which might be related with apoptosis induction via EGFR/PPARγ/PI3K/AKT pathway.